Gravel Parameterization Schemes and its Regional Assessment on Tibetan Plateau Using RegCM4. (13th July 2021) - Liu, Yigang; Lyu, Shihua; Ma, Cuili; Xu, Yue; Luo, Jiangxin
Abstract: In this study, the impact of gravel was taken into account in the regional climate model version 4.7, which was driven by the ERA‐Interim with a resolution of 1.5 km in this numerical experiment. The gravel parameterization schemes and the original soil hydrothermal parameterization schemes were used in the regional soil hydrothermal simulations on the Tibetan Plateau (TP), respectively. The performance of the two schemes in simulating the soil moisture (SM) was assessed. Moreover, three areas were selected in terms of the distribution of gravel content on the TP to investigate the differences in the internal mechanism of the model between the two schemes. The performance of the gravel schemes in simulating SM is generally improved compared with that of the original schemes. The simulation effect is superior in the southeastern TP. Except for the southeastern TP, the performance in simulating the temporal variations of SM below the soil depth of 1.0 m still needs to be improved. The fractional saturated area ( f sat ) and the fraction of the inundated area ( f h2osfc ) are two pivotal variables that control the important component of the hydrologic process. There may be a threshold for the increase of f h2osfc, when the increase of f h2osfc is lower than this value, the main effect of increasing f h2osfc is to reduce the surface moisture that is, divided into the input of soil. However, when the increase of f h2osfc is higher than this value, the main effect of increasing f h2osfc is to increase the bottom drainage from the surface water store. The increasing gravel content will induce the decreasing mineral soil saturated hydraulic conductivity, which leads to SM increases, the opposite is true. Plain Language Summary: Often referred to as the "Third pole" or the "water Tower of Asia, " the Tibetan Plateau (TP) is the source region of major rivers in Asia. Its hydrological processes exert a great impact on the Ecological environment and the Socio‐economic development of the watershed and the lower reaches. Therefore, it is necessary to understand the change regularity and mechanism in the hydrological processes of the TP. But limited by the environmental conditions, the in‐situ observations used in the research of the TP are very scarce, thus it is an effective complementary approach to investigate the hydrological processes of the TP using the land surface or hydrological models that are vigorously evaluated. However, there are many problems in the land surface models coupled into the climate models concerning the parameterizations of the TP soil, one of them is ignoring the gravel which widely distributed in the TP. In this study, the impact of gravel is taken into account in regional simulations on the TP, the results show that the accuracy of the simulation has been improved significantly. Key Points: The impact of gravel is taken into account in the regional soil hydrothermal simulation on the Tibetan Plateau The gravel schemes generally perform better than the original schemes in reproducing the soil moisture on the Tibetan Plateau